Attitudes of English language faculty in three leading Philippine universities toward Philippine English - Bautista, Ma. Lourdes S. (Animo Repository, 2001)
Although a number of studies have been done on the structure of Philippine English and the acceptability and comprehensibility of certain of its lexical and grammatical features, no study has been done on the acceptability of Philippine English as a whole, as a variety. This paper investigated the attitudes toward Philippine English of 88 English Language Department faculty members at the Ateneo de Manila University, De La Salle University-Manila, and the University of the Philippines in Diliman, the three leading universities of the Philippines, using free choice and Likert Scale items adapted from Baumgardner (1995) for Pakistani English and Crismore et al. (1996) for Malaysian English. The findings revealed that the faculty had very positive feelings toward Philippine English as a variety (e.g., strongly disagreeing with the statement that “Philippine English is actually mistakes made by people who speak poor English”), much more positive than those found in the Pakistani and Malaysian studies, but that they had reservations toward certain ungrammatical or unidiomatic expressions used in Philippine English. A brief discussion exploring the basis of this ambivalence forms the conclusion of the paper. © 2001 ALC Press, Inc.